Effects of Story Mapping on EFL Speaking Fluency and Comprehensibility: A Quasi-Experimental Study of Tenth-Grade Students - Nirma Kartikasari; Konder Manurung; Maf’ulah Maf’ulah; Abd. Kamaruddin (Journal of General Education and Humanities, 2026)
This research investigates the effectiveness of the story-mapping technique in improving the speaking skills of tenth-grade students at SMA Negeri 1 Sindue. The study was conducted because many students faced challenges in speaking English, such as limited vocabulary, pronunciation difficulties, low confidence, and fear of making mistakes. A quantitative approach with a quasi-experimental pre-test and post-test control group design was employed. The sample consisted of two classes: the experimental group (n = 34), which was taught using story mapping, and the control group (n = 36), which received the oral presentation method, in which students practised speaking by presenting material orally in front of the class. Students’ speaking skills were assessed for fluency and comprehensibility by two trained raters specialising in speaking with, and the scores maintained scoring reliability. The descriptive statistics showed that the experimental group achieved a notable improvement, with the mean score increasing from 42.06 in the pre-test to 52.35 in the post-test, whereas the control group showed no meaningful change. The Mann-Whitney U Test further confirmed a significant difference between the groups, indicated by an Asymp. Sig. value of 0.004, supported by a medium effect size (r = 0.34). These findings demonstrate that story mapping helps students organise ideas more effectively, speak more fluently, and express thoughts more clearly. Therefore, story mapping is considered an effective technique for enhancing speaking skills and is recommended for use in an English-speaking classroom.